RELIABILITY OF CONSTRUCTIONAL PRODUCTION LINE - Bredikhina , Natalia (Journal of Applied Engineering Science, 2020)
The article discusses the most important quantitative characteristics of the reliability of constructional production line. The reliability of constructional production line, in the general case, is understood as its property to maintain its parameters in permissible, predetermined limits. One of the main parameters of constructional production line is its intensity. In addition, intensity is one of the main indicators characterizing the efficiency of the production line. Generally speaking, efficiency serves as a measure of system productivity taking into account the external environment. Therefore, in a particular case, the reliability of constructional production line can be understood as the stability of its intensity.